2019
DOI: 10.1253/circj.cj-18-1269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Coronary Computed Tomography Angiography-Derived Fractional Flow Reserve on Japanese Population in the ADVANCE Registry

Abstract: tional guidelines strongly endorse invasive FFR in the management of CAD patients. 4 However, the adoption of FFR is limited in the real world and its invasive nature is thought to be a major hindrance to its use. 5 Coronary computed tomography angiography (cCTA)-P hysiological assessment is paramount in the management of patients with coronary artery disease (CAD). Invasive fractional flow reserve (FFR) has proven to have excellent diagnostic accuracy and to improve the clinical outcome. 1-3 As a result, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…When stratified by FFRCT, similar rates of revascular- of core laboratory-determined treatment plans. 6 The reclassification rate was lower in the present study for non-AUC sites, likely reflecting the lower anatomical coronary disease burden identified on CCTA, with lower rates of anatomical stenosis at non-AUC sites. These findings are in agreement with the growing clinical evidence regarding the use of CCTA in clinical practice, where CCTA has been shown to be a powerful tool for the detection or exclusion of anatomical coronary disease but unable to adjudicate the physiological significance of CAD.…”
Section: Downstream Clinical Treatment Stratified By Ffrctcontrasting
confidence: 50%
See 1 more Smart Citation
“…When stratified by FFRCT, similar rates of revascular- of core laboratory-determined treatment plans. 6 The reclassification rate was lower in the present study for non-AUC sites, likely reflecting the lower anatomical coronary disease burden identified on CCTA, with lower rates of anatomical stenosis at non-AUC sites. These findings are in agreement with the growing clinical evidence regarding the use of CCTA in clinical practice, where CCTA has been shown to be a powerful tool for the detection or exclusion of anatomical coronary disease but unable to adjudicate the physiological significance of CAD.…”
Section: Downstream Clinical Treatment Stratified By Ffrctcontrasting
confidence: 50%
“…For example, a positive FFRCT result was associated with higher rates of ICA showing obstructive CAD and subsequent coronary revascularization, whereas patients with a negative FFRCT result were managed with medical therapy and deferral of ICA, with demonstrable favorable short-term clinical outcomes. 6 FFRCT has recently received funding and support from the Ministry of Health, Labour and Welfare (MHLW) in Japan, but only at approved sites that have satisfied the hospital conditions required by appropriate use criteria (AUC) defined by the MHLW. AUC sites are defined by the MHLW as training facilities of the Japanese Circulation Society (JCS), Japanese Association of Cardiovascular Intervention and Therapeutics (CVIT), and Japan Radiological Society (JRS).…”
Section: Discussionmentioning
confidence: 99%
“…With FFR set as the baseline, a study showed that QFR had a positive discovery rate of 81% and a negative predictive value (NPV) of 90%, whereas CT-FFR had a positive predictive value (PPV) of 70% and an NPV of 82% ( 41 ). Despite the better potential in diagnostic accuracy of QFR, by contrast, CT-FFR is more appropriate for outpatients without evident coronary syndrome to reduce unnecessary ICA ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a noninvasive test following CCTA, FFR CT assesses functional severity by utilizing computational fluid dynamics to calculate coronary blood flow, and exhibits good correlation with invasive FFR 16 . The utility of FFR CT has been demonstrated in several studies of patients with suspected CAD and CAS, and FFR CT ≤0.80 was used as a predictive indicator with functional significance 16‐18 . Data on clinical outcomes in association with FFR CT are limited compared to the diagnostic data.…”
Section: Discussionmentioning
confidence: 99%
“… 16 The utility of FFR CT has been demonstrated in several studies of patients with suspected CAD and CAS, and FFR CT ≤0.80 was used as a predictive indicator with functional significance. 16 , 17 , 18 Data on clinical outcomes in association with FFR CT are limited compared to the diagnostic data. Therefore, the FFR CT analysis was performed in patients with CAS determined using CCTA among a cohort of patients with suspected CAD in the present study, and the utility of FFR CT in predicting downstream clinical outcomes was examined.…”
Section: Discussionmentioning
confidence: 99%